Growth of Prototheca isolates on n-hexadecane and mixed-hydrocarbon substrate. - Walker, J D (1978)
Prototheca zopfii, an achlorphyllous alga, was capable of using hydrocarbons as sole carbon and energy source. The ability of P. zopfii to use hydrocarbons did not correlate with source of isolation. Seventy-five percent of the P. zopfii cultures recovered from sewage, plants, or animals utilized hydrocarbons. Other Prototheca species and P. zopfii that did not utilize hydrocarbons were isolated simultaneously from several sources with isolates that did use hydrocarbons. Species type rather than source of isolation was the predominant factor that determined hydrocarbon utilization.